2007
DOI: 10.1177/030089160709300609
|View full text |Cite
|
Sign up to set email alerts
|

Natural Fluorescence Spectroscopy of Human Blood Plasma in the Diagnosis of Colorectal Cancer: Feasibility Study and Preliminary Results

Abstract: These results, although preliminary, suggest the potential of fluorescence measurements of blood plasma as an additional method for diagnostic application in colon cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 15 publications
1
26
0
2
Order By: Relevance
“…Pathologic tissue changes cause an alteration of the histologic organization and changes in biochemical and physiochemical properties mainly due to collagen, elastin, nicotinamide adenine dinucleotide, porphyrin and flavin adenine dinucleotide (FAD) composition, which are reflected in an altered fluorescence emission spectrum. 10 Near-infrared spectroscopy uses the absorption profiles of DNA/RNA, carbohydrates, lipids, proteins, and water to provide information about molecular composition and the biological profile of tissues. 8 Both optical spectroscopy methods have shown a great potential in the discrimination of malignant and benign tissue and have been applied in colorectal, breast, prostate, and lung cancer research.…”
Section: Introductionmentioning
confidence: 99%
“…Pathologic tissue changes cause an alteration of the histologic organization and changes in biochemical and physiochemical properties mainly due to collagen, elastin, nicotinamide adenine dinucleotide, porphyrin and flavin adenine dinucleotide (FAD) composition, which are reflected in an altered fluorescence emission spectrum. 10 Near-infrared spectroscopy uses the absorption profiles of DNA/RNA, carbohydrates, lipids, proteins, and water to provide information about molecular composition and the biological profile of tissues. 8 Both optical spectroscopy methods have shown a great potential in the discrimination of malignant and benign tissue and have been applied in colorectal, breast, prostate, and lung cancer research.…”
Section: Introductionmentioning
confidence: 99%
“…Algorithms such as principal components analysis (PCA) [12], linear discriminant analysis (LDA) [13], and partial least-squares (PLS) [14] were often used combined with those spectral features. But those parameters can only provide limited information about the whole spectra, neglecting others such as fluorescence background which has been used on the blood for the diagnosis of several cancers [6,15]. Richer information will be obtained using both the features of Raman and the background fluorescence spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies had been reported on the native fluorescence spectroscopy of various tissues (2,3,(29)(30)(31). As any metabolic changes in the body may reflect in the body fluids, attempts have also been made on the characterization of body biofluids, viz., blood in diagnosis of liver diseases and cancer (1,14). It has also been reported that urine is a diagnostically important biofluids, which has many metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Although many applications of native fluorescence spectroscopy of biomolecules are reported on the characterization of cellular metabolic pathways and the discrimination of malignant from normal conditions of tissues, only limited studies have been reported on the applications of native fluorescence spectroscopy of biofluids in diagnostic oncology. Only limited data are available on the optical spectroscopic characterization of body biofluids such as blood (1,(12)(13)(14), saliva (15,16) and urine (17,18). Although Leiner et al has discussed the possible shoulder emission spectra of various molecules at different excitation and emission ranges, they have not compared cancer samples with normal urine samples (17).…”
Section: Introductionmentioning
confidence: 99%